Application of Registration of Transfer of Rights Due to Direct Inheritance with Deed of Distribution of Inheritance (Study at Land Offices Throughout Malang) - Intan Tresna Sari Rosita; Imam Kuswahyono; Hariyanto Susilo (Jurnal Multidisiplin Madani, 2023)
The problem of transitional registration is one of the typologies of land cases that often occurs. Registration of transfer of rights due to inheritance is currently not understood equally by the government, especially in the implementation of registration of transfer of rights due to direct inheritance with the deed of distribution of inheritance. For this reason, this paper will try to conduct a legal study regarding the effectiveness of Article 111 paragraph (5) of the ATR/Ka.BPN Regulation Number 16 of 2021 as the legal basis for carrying out transitional registration at Land Offices throughout Malang Raya. This paper uses the socio-legal method with an empirical and normative approach. The results of the research show that the registration of the transfer of rights due to direct inheritance with the deed of distribution of inheritance based on Article 111 paragraph (5) of Permen ATR/Ka.BPN 16 of 2021 is not effective at the Land Office in Malang Raya. There are several reasons, first, administrative habits that have been carried out by transferring inheritance first to all heirs based on the Declaration of Heirs, then transferring to one of the heirs based on APHB. Second, the record problem. Third, the problem of local taxes that will be reduced. The ineffectiveness of this article can harm interested parties because it can be detrimental in terms of time and costs when registering the transfer of rights due to inheritance